Pengabdian Berbasis Masjid: Meningkatkan Kesejahteraan dan Religiusitas Desa Keban Agung - Hamdan Hamdan; Sugiyono Purnomo; Rizki Febriansyah; Nesi Purnama Sari; Levia Afani; Kamalat Azaliah (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
The community of Keban Agung Village faces significant challenges related to social welfare and religious engagement. Despite the central role of the mosque as a community hub, participation in religious activities and access to social programs remain limited. This study aimed to enhance social welfare and religious commitment through a mosque-based community service program. The program included activities such as religious competitions, educational support, health services, and social welfare initiatives. A participatory approach was employed, involving local residents and mosque management in the design and implementation of activities. Data were collected through direct observation, interviews, and documentation, and were analyzed descriptively. The results indicated a marked improvement in community participation in religious and social activities, contributing to both social cohesion and spiritual growth. The study highlights the importance of mosque-centered initiatives in addressing community needs and fostering a stronger sense of collective well-being.